Transparent and conductive Al‐doped ZnO films for solar cells applications. Issue 4 (4th December 2012) - Grilli, Maria Luisa; Sytchkova, Anna; Boycheva, Sylvia; Piegari, Angela
Abstract General rules governing the quality of aluminium‐doped zinc oxide films (Al:ZnO, AZO) grown by radio frequency sputtering were searched. A vast set of experimental data on the electrical, optical, structural, and morphological properties of AZO films prepared at different deposition conditions was analyzed. AZO films with a high Haacke's figure of merit ΦTC = 10 m Ω−1 were fabricated at temperatures lower than 250 °C starting from a target of ZnO mixed with 2 wt% Al2O3. It was demonstrated that AZO films with similar good optical and electrical properties can be obtained in different ways by opportunely combining the deposition parameters, proving that AZO film characteristics depend on the energy efficiency of the deposition process, which can be ensured at different deposition conditions. It was found that the temperature and the magnetron strength are essential for the growing process to guarantee film optimal performances, while the other deposition parameters can be opportunely adjusted for tuning the film characteristics. A correlation between electrical, structural and microstructural characteristics of the films was established.